Implementation of the Smart Mobility Concept in the Public Transportation System (Case Study on Transjakarta Services) - Aulia Yuniar; Mita Mulyana Sari; Rieka Adelia; Intan Nurfadhillah; Annisa Putri; Irvan Arif Kurniawan (Sean Institute, 2026)
Rapid urbanisasi poses complex challenges in managing the mobility of populations in large cities, especially in transportasi publik. This article examines the implementation of the Smart Mobility concept within the sistem transportasi publik TransJakarta, which is part of efforts to realize a livable, productive, and sustainable city. The study uses a qualitative descriptive approach with observation, documentation, and interviews with active users. The results show that TransJakarta has successfully integrated digital technologies such as e-ticketing, real-time tracking, and the use of environmentally friendly fleets with electric buses. Nevertheless, challenges remain, including uneven distribution of stops and fleets, limited facility quality, issues with infrastruktur TIK, as well as safety and operational management aspects that need improvement. In conclusion, the development of a public transportation system based on Smart Mobility in Jakarta must be supported by sustainable maintenance, integrated technological innovation, driver training, and predictive data management to provide inclusive, safe, responsive, and globally competitive services.